is fixed at the origin.
Thank you for the opportunity to help you with your question!
force due to the charged particle F = k(q1)(q2)/(r^2) and force due to gravity F = mg
k = 1.38*10^-23 J/K , g = - 9.81 m/s^2
m = 1.67*10^-27 kg, q2 = 9.11*10^31 C
but F(charge) = F(g) thus k(q1)(q2)/(r^2) = mg
convert nC to C q1 = -3.6*10^-10
r = sqrt(k(q1)(q2)/(m*g)) = sqrt ((1.38*10^-23)(-3.6*10^-10)(9.11*10^31)/(1.67*10^-27)(- 9.81)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?